2017
DOI: 10.1038/s41467-017-01829-1
|View full text |Cite
|
Sign up to set email alerts
|

The IKK/NF-κB signaling pathway requires Morgana to drive breast cancer metastasis

Abstract: NF-κB is a transcription factor involved in the regulation of multiple physiological and pathological cellular processes, including inflammation, cell survival, proliferation, and cancer cell metastasis. NF-κB is frequently hyperactivated in several cancers, including triple-negative breast cancer. Here we show that NF-κB activation in breast cancer cells depends on the presence of the CHORDC1 gene product Morgana, a previously unknown component of the IKK complex and essential for IκBα substrate recognition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 68 publications
4
68
0
Order By: Relevance
“…The activation of NF‐kappa B induced the formation of the IKK (IκB kinase) protein complex and some protein regulate the complex as IKK interactors, such as Hsp70, Hsp90. And some NF‐kappa B targeted genes promote tumor growth, invasion and metastasis, such as MMP‐9 and IL‐6 . There are reports shown that CD147 promoted the expression of MMP‐9, which might be a mechanism that CD147 promoted tumor progression and invasion in HNSCC via regulating NF‐kappa B signaling .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The activation of NF‐kappa B induced the formation of the IKK (IκB kinase) protein complex and some protein regulate the complex as IKK interactors, such as Hsp70, Hsp90. And some NF‐kappa B targeted genes promote tumor growth, invasion and metastasis, such as MMP‐9 and IL‐6 . There are reports shown that CD147 promoted the expression of MMP‐9, which might be a mechanism that CD147 promoted tumor progression and invasion in HNSCC via regulating NF‐kappa B signaling .…”
Section: Discussionmentioning
confidence: 96%
“…The mechanisms underlying CD147 induced activation of NF‐kappa B in HNSCC were still not clear. Reports showed that different stimuli could activate the NF‐kappa B signaling, including cytokine, growth factor, DNA damages and oncogenic stress . The activation of NF‐kappa B induced the formation of the IKK (IκB kinase) protein complex and some protein regulate the complex as IKK interactors, such as Hsp70, Hsp90.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 1 μg of total RNA was used for reverse transcription with iScript cDNA Synthesis Kit (Bio-Rad) according to the manufacturer's protocol. 21 1 μg of total RNA was used for reverse transcription with iScript cDNA Synthesis Kit (Bio-Rad) according to the manufacturer's protocol.…”
Section: Gene Expression Analysismentioning
confidence: 99%